Working with Cancer: Health and Disability Disparities among Employed Cancer Survivors in the U.S. - Clarke, Tainya C. (2011)
INTRODUCTION: Approximately 40% of Americans annually diagnosed with cancer are working-age adults. Using a nationally representative database, we characterized differences in health status and occupation of working cancer survivors and persons without cancer. METHODS: Cross-sectional data pooled from the 1997–2009 US National Health Interview Survey for adults with self-reported physician-diagnosed cancer (n=22,952) and those without (n=358,495), were analyzed. Multivariable logistic regression was used to compare the health and disability status of employed cancer survivors across occupational sectors relative to workers without a cancer history and unemployed cancer survivors. RESULTS: Relative to workers with no cancer history, cancer survivors were more likely to be white-collar workers and less likely to be service workers. Working cancer survivors were significantly less likely than unemployed survivors, but more likely than workers with no cancer history, to report poor-fair health (0.25; 0.24–0.26) and (2.06;1.96–2.17) respectively, and ≥2 functional limitations (0.37;0.35–0.38) and (1.72;1.64–1.80) respectively. Among employed cancer survivors, blue-collar workers reported worse health outcomes, yet they reported fewer workdays missed than white-collar workers. CONCLUSION: Blue-collar cancer survivors are working with high levels of poor health and disability. These findings support the need for workplace accommodations for cancer survivors in all occupational sectors, especially blue-collar workers.